Post-presumption argumentation and the post-truth world: on the conspiracy rhetoric of Donald Trump. (3rd July 2019) - Neville-Shepard, Ryan
Abstract: Building on the notion of post-truth, this essay suggests that Donald Trump—both as a candidate and president—has crafted a notion of post-presumption argumentation. While there are many theories of how presumption functions in argumentation, scholars agree that it is largely a procedural device meant to promote deliberation. The essay suggests that post-presumption argumentation has become a new model—rising partly from a cultural shift triggered by rampant conspiracy theorizing by political and social elites—that undercuts the presumption of veracity, undermines faith in institutions that give presumptions force, and rejects deliberation as a communal goal.